Improving Student Learning Outcomes Using Active Learning Methods in Learning Moral Creeds at MAS Al-Wasliyah 26 Tinokkah Sipispis District Serdang Bedagai Regency - Saragih, Rina Ihwani (Yayasan Salam Cerdas Al-Fattah, 2023)
Effective learning depends on methods, and not all learning methods are suitable for all fields, especially moral beliefs which talk about something abstract. This research aims to find out how efficient the implementation of the active learning method is in improving student learning outcomes in learning moral beliefs in class. This research is field research by taking data sources from students, moral aqidah teachers, school principals and implementing active learning methods in improving the learning outcomes of class X MAS Al-Wasliyah 26 Tinokkah students as well as documentation. The data collection methods used are observation, interviews, documentation and questionnaires. The data analysis method used is descriptive analytic. From the research results, it was concluded that the implementation of active learning methods influenced the learning intensity of class X students at MAS Al-Wasliyah 26 Tinokkah. With interesting learning methods, students become more interactive and easily understand related material, moral beliefs. The teacher's efforts to improve the learning outcomes of moral beliefs in class